2021
DOI: 10.1186/s42506-021-00096-9
|View full text |Cite
|
Sign up to set email alerts
|

A semi-systematic review on hypertension and dyslipidemia care in Egypt—highlighting evidence gaps and recommendations for better patient outcomes

Abstract: Background Both hypertension and dyslipidemia are considered as major modifiable risk factors of cardiovascular diseases (CVDs), and their prevalence in Egypt has increased in recent years. Evidence-based systematic evaluation of data on hypertension and dyslipidemia is critical for effective patient-centric management to reduce the overall risk of CVDs in Egypt. This semi-systematic review aimed to quantify and identify data gaps in the prevalence and distribution of patient journey touchpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 93 publications
0
6
1
Order By: Relevance
“…A Palestinian study conducted on healthy men (n=140) reported that the overall prevalence of dyslipidemia was 66.4% and hypo HDL was the most prevalent type of dyslipidemia (59.3%), which was followed by hypertriglyceridemia (20%) (25). In contrast, dyslipidemia prevalence was 78.7% in men and 80.4% in women in Turkish adults (26), 33% in Saudi adults (27), and 36.8% in Egyptian adults (28), which may reflect different genetic predispositions, socioeconomic status, and lifestyles of the studied subjects. Another Palestinian study revealed that hypo HDL was highly prevalent among obese and normal-weight adults indicating that factors other than BMI and central obesity could influence hypo HDL in Palestinians; the study revealed a significant association of hypo HDL with marital status, tobacco smoking, and occupational exposure to pesticides (29).…”
Section: Discussionmentioning
confidence: 99%
“…A Palestinian study conducted on healthy men (n=140) reported that the overall prevalence of dyslipidemia was 66.4% and hypo HDL was the most prevalent type of dyslipidemia (59.3%), which was followed by hypertriglyceridemia (20%) (25). In contrast, dyslipidemia prevalence was 78.7% in men and 80.4% in women in Turkish adults (26), 33% in Saudi adults (27), and 36.8% in Egyptian adults (28), which may reflect different genetic predispositions, socioeconomic status, and lifestyles of the studied subjects. Another Palestinian study revealed that hypo HDL was highly prevalent among obese and normal-weight adults indicating that factors other than BMI and central obesity could influence hypo HDL in Palestinians; the study revealed a significant association of hypo HDL with marital status, tobacco smoking, and occupational exposure to pesticides (29).…”
Section: Discussionmentioning
confidence: 99%
“…The death rate of 40% each year. Egypt, being the most populated country in the Middle East and North Africa region, accounted for all CVD deaths in regions 6 , 5 . And according to WHO, Egypt estimated adult people suffering from hypertension in 2017 was (29.2%) and in 2020, the total percentage of death from hypertension (was 3.93%) of total death.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic hypertension increases risk of ischemic heart diseases, ischemic brain disorders and renal failure (1) . The prevalence of hypertension was estimated up to 59% in Egypt (2) . It is characterized by structural and functional abnormalities in the microcirculation, including microvascular rarefaction and diminished circulatory efficiency, which eventually result in organ failure (3) .…”
Section: Introductionmentioning
confidence: 99%